PHYTOPLANKTON SPECIES COMPOSITION AND BIODIVERSITY INDICES IN AUDA MARSH- SOUTHERN IRAQ - & et al., Albueajee (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigate the trophic status of the marshes by phytoplankton diversity. The Phytoplankton community and four biodiversity indices were studied in Auda marsh southern Iraq in the period between January 2018 to January 2019. A total of 146 species were identified belonging to 8 classes as follows: Bacillariophyceae (85 taxa), Euglenophyceae (26 taxa), Cyanophyceae (16 taxa), Chlorophyceae (11 taxa), Mediophyceae (3 taxa), Coscinodiscophyceae (2 taxa), Conjugatophyceae (1 taxa), Trebouxiophyceae (1 taxa), and Dinophyceae (1 taxa). The most predominant diatom was Nitzschia (15 species), and followed by the other genera Phacus (11 species), Navicula and Euglena (10 species). The Shannon-Weiner diversity, Richness index and Evenness index were recorded a low value in wet 2019 and a high values in wet (for Shannon Weiner and Evenness indices) and dry ( for Weiner and Evenness indices) 2018. The Jaccard index showed equal similarity between study sites, while the highest seasonal similarity was recorded between wet and dry 2018 and lowest similarity was between wet2018 and wet2019. According to the biodiversity indices Auda marsh has high diversity. The results revealed that Auda marsh is mesotrophic according to phytoplankton species composition.